2012
DOI: 10.1371/journal.pone.0035031
|View full text |Cite
|
Sign up to set email alerts
|

Functional and Structural Analysis of the Internal Ribosome Entry Site Present in the mRNA of Natural Variants of the HIV-1

Abstract: The 5′untranslated regions (UTR) of the full length mRNA of the HIV-1 proviral clones pNL4.3 and pLAI, harbor an internal ribosomal entry site (IRES). In this study we extend this finding by demonstrating that the mRNA 5′UTRs of natural variants of HIV-1 also exhibit IRES-activity. Cap-independent translational activity was demonstrated using bicistronic mRNAs in HeLa cells and in Xenopus laevis oocytes. The possibility that expression of the downstream cistron in these constructs was du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
71
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(79 citation statements)
references
References 71 publications
(205 reference statements)
8
71
0
Order By: Relevance
“…1A). A similar strategy has been successfully used in previous studies (12,15,16,32). In this context the translational activity of the HTLV-1 5=UTR was measured by using FLuc activity as the readout, while the RLuc reporter gene was translated by a capdependent mechanism and serves as an internal control.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…1A). A similar strategy has been successfully used in previous studies (12,15,16,32). In this context the translational activity of the HTLV-1 5=UTR was measured by using FLuc activity as the readout, while the RLuc reporter gene was translated by a capdependent mechanism and serves as an internal control.…”
Section: Resultsmentioning
confidence: 99%
“…8A), were transfected into HeLa cells. Even though HeLa cells are not the natural target of HTLV-1, they were selected for these assays since they are easy to handle and modify (see the RPS25 data presented below), efficiently transfected, known to support IRES activity from other retroviral mRNAs, including that of the HIV-1 IRES (12,14,15), and HeLa cell extracts enhance HTLV-1 IRES activity (Fig. 5B).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…86,87 The IRES within the 5 0 UTR has been evidenced in the laboratory adapted HIV-1 infectious recombinant proviral clone NL4.3, the CXCR4 (X4)-tropic primary isolate HIV-LAI and in the 5 0 UTR of viral RNA isolated from clinical samples. 86,88,89 The characterization of the HIV-1 IRES was done by using a series of bicistronic constructs that were verified to contain no cryptic promoter or spurious splice sites as they are often a caveat in this area of research 86,[88][89][90] In addition, translation of HIV-1 in a bicistronic context was shown to be resistant to picornaviral proteases that specifically inhibit cap-dependent translation initiation. 86,89,91 More recently, Monette et al have used transfection-infection experiments of DNA encoding a bicistronic RNA containing the HIV-1 5 0 UTR proving that its activity is not disrupted by poliovirus infection in 293 T cells.…”
Section: Characterization Of Ires Sequencesmentioning
confidence: 99%